Online Learning And Quality Of Education During Covid-19 Pandemic: Evidence From Pakistani Universities (Journal of Namibian Studies : History Politics Culture, 2023)
This study examines how online learning improves teacher competence, family cooperation, educational quality, and environmental impact in Pakistan during the COVID-19 pandemic. A self-administered questionnaire was given to Pakistani university students, and 296 replies were collected via purposive sampling. PLS-SEM was employed in the investigation using Smart-PLS 3.2.8. Results show that online education increased environmental quality during the COVID-19 epidemic. During this pandemic, family engagement was positively connected with online learning effectiveness. Online learning affected education quality during the COVID-19 epidemic. It was shown to improve educators' skills.